Back to the pre-industrial age? FAOSTAT statistics of food supply reveal radical dietary changes accompanied by declining body height, rising obesity rates, and declining phenotypic IQ in affluent Western countries - Pavel Grasgruber (Annals of Medicine)
Meta-analyses of observational and clinical studies conducted in recent years have raised serious doubts about the validity of the low-fat dietary recommendations introduced in the late 1970s/early 1980s, due to the absence of any convincing link between saturated fat and the risk of cardiovascular diseases. At the same time, long-term food supply statistics from the FAOSTAT database show that these recommendations were at the root of fundamental dietary changes in Western countries, which resulted in a lower consumption of eggs and red meat, a higher consumption of cereals and poultry, a decline in average protein quality and, overall, in a higher glycemic load of the diet. Because current views on human nutrition are based primarily on highly unreliable questionnaire data from observational studies, the purpose of this commentary is to provide an alternative ecological (country-level) perspective and to trace the consequences of these nutritional changes using the FAOSTAT database in combination with available anthropological and health statistics. This comparison shows a close connection between the decline in protein quality and the sudden reversal of the positive height trend in some Western countries, after ∼150 years of continuous growth, which points to suboptimal levels of child nutrition. The sharp increase in the prevalence of obesity and type 2 diabetes is strongly correlated with the increasing consumption of high-glycemic carbohydrates and sweeteners, and is also interconnected with the decrease in body height, because a high-quality, growth-stimulating diet during adolescence is inversely related to obesity. Given the long-term association between height and phenotypic IQ, the lower quality of nutrients in children’s diet may also seriously affect intellectual potential and future civilizational development. In light of these findings, current nutritional strategies should be seriously reconsidered and recommended protein intakes for children must be urgently reevaluated.